Tunable green/red dual-mode luminescence via energy management in core-multishell nanoparticles. (15th August 2018) - Leng, Zhihua; Li, Liping; Zhang, Dan; Li, Guangshe
Abstract: Achieving up-conversion luminescence from Tb 3+ /Eu 3+ ions was generally via a complicated energy transfer process (Yb 3+ → Tm 3+ → Gd 3+ → Ln 3+, Ln = Tb/Eu), which makes the relevant energy management rather difficult and inevitably results in impure blue luminescence of Tm 3+ . In this work, a facile and rational strategy is designed to integrate dual-mode luminescence from Eu 3+ /Tb 3+ ions into NaGdF4 :Yb/Eu@NaGdF4 :Ce@NaGdF4 :Yb/Tb@NaYF4 core-multishell nanostructure. It is found that the down-conversion energy transfer across NaGdF4 @NaGdF4 interface is confined in a narrow space region of approximately 2 nm. For the up-conversion mode, the primary factor that dominates the emission intensity of Eu 3+ is determined to be the molar ratio of NaGdF4 :Yb/Tb component in the second shell to NaGdF4 :Yb/Eu one in the core, which differs from the anisotropic filtration effect previously reported. Eventually, tunable dual-mode emission colors were achieved through simply varying the inner shell thickness of NaGdF4 :Yb/Tb. The strategy of integrating dual-mode luminescence of Eu 3+ /Tb 3+ reported here for energy management allows one to design new luminescence materials for many important applications. Graphical abstract: Unlabelled Image Highlights: NaGdF4 :Yb/Eu@NaGdF4 :Ce@NaGdF4 :Yb/Tb@NaYF4 was prepared for dual-model emission. Molar ratio of NaGdF4 :Yb/Eu to NaGdF4 :Yb/Tb dominates the UC emission intensity. Eu 3+ and Tb 3+ share the UV excitation energy from same NaGdF4 :Ce shell.